Dravet Syndrome in Lebanon: First Report on Cases with SCN1A Mutations - Saada Alame; Eliane El-Houwayek; Caroline Nava; Sandra Sabbagh; Ali Fawaz; Anne-Celine Gillart; Dana Hasbini; Christel Depienne; André Mégarbané (Case Reports in Medicine)
Dravet syndrome, also known as severe myoclonic epilepsy in infancy, is a rare disease characterized by the appearance of different types of seizures in a healthy baby, triggered by various factors and stressful events. We report 8 Lebanese cases referred for molecular analysis of the SCN1A gene. Results were positive in 7 cases and revealed de novo variants at the heterozygous state in different exons of the gene for all except one, where the variant was intronic. Four variants were novel. Confirmation of Dravet syndrome is important for a better follow-up and treatment, preventing the occurrence of status epilepticus and severe neurological deterioration.